EDUKASI PENINGKATAN PERILAKU CUCI TANGAN PAKAI SABUN PADA SISWA TAMAN KANAK-KANAK DI KOTA PADANG - Syafrawati Syafrawati; Rayunda Chikita Oktari (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Inappropriate Handwashing with Soap (HIS) behavior is still high in children aged ten years and under. The results showed that there was a relationship between the behavior of washing hands with soap and diarrhea in children. Diarrhea is still included in the order of 10 most diseases in Padang city. This activities aims to improve (HIS) behavior in Kindergarten students. The activity targets kindergarten students in Nanggalo District, Padang City, namely Arrozaq Islamic Kindergarten and Nurul Halim Islamic Kindergarten, totaling 66 people. The activity began with introductions, providing information about the importance of (HIS) and showing a video containing a short drama about the importance of (HIS), the consequences if not (HIS), and (HIS) dance. (HIS) dance teaches how to wash hands with soap properly and correctly. After that, good and correct (HIS) practice was carried out. Health promotion using dance and singing media got a good response from kindergarten students. Participants paid close attention to the information provided and were enthusiastic in carrying out activities, especially in the socialization of (HIS) dance. It is hoped that this activity can take place on an ongoing basis for all kindergarten students in Padang city, considering that the requirement for applying for kindergarten accreditation is the availability of (HIS) equipment in schools. Therefore, it is hoped that there will be continuous training for students about (HIS).